Screening for Polymorphism, Cyclodextrin Complexation, and Co-Crystallization of the Non-Steroidal Anti-Inflammatory Drug Fenbufen: Isolation and Characterization of a Co-Crystal and an Ionic Co-Crystal of the API with a Common Coformer - Hannah M. Frösler; Neo Refiloe Mancapa; Laura Catenacci; Milena Sorrenti; Maria Cristina Bonferoni; Mino R. Caira (Pharmaceutics)
Background/Objectives: Increasing the solid-state landscape of an active pharmaceutical ingredient (API) by generating new crystalline forms (e.g., polymorphs, cyclodextrin (CD) inclusion complexes, co-crystals, and salts) can yield products with significantly enhanced biopharmaceutical properties (especially increased water solubility), thereby improving API delivery and extending its lifetime. The aim of this study was the isolation of new solid forms of the poorly water-soluble non-steroidal anti-inflammatory drug fenbufen (FBF), for which relatively few solid phases have been reported to date. Further motivation for the study is the recent finding that it has potential for repurposing to treat acute pancreatitis. Methods: Interventions for generating new solid forms of FBF included (a) polymorph screening with a variety of solvent media, (b) attempts to form solid inclusion complexes with the native cyclodextrins α-, β-, and γ-CD using various preparative methods, and (c) co-crystallization with a series of coformers to produce co-crystals and/or molecular salts. Results: No new polymorphic forms of FBF were identified, but screening with CDs resulted in isolation and characterization of a new solid inclusion complex with γ-CD. However, co-crystallization of FBF with the water-soluble coformer isonicotinamide yielded two new products, namely a 1:1 co-crystal and an unusual multi-component ionic co-crystal, whose aqueous solubility indicated significant enhancement of FBF solubility. Conclusions: Due to its extremely low water solubility, FBF presented challenges during the study aimed at modifying its crystalline form. However, two new supramolecular forms, a co-crystal and an ionic co-crystal, were isolated, the latter phase having potential for further formulation owing to its significantly enhanced solubility.